Dementia in People with Severe/Profound Intellectual (and Multiple) Disabilities: Practice-Based Observations of Symptoms. Issue 4 (2nd October 2022) - Wissing, Maureen B.G.; Fokkens, Andrea S.; Dijkstra, Roos; Hobbelen, Johannes S.M.; van der Putten, Annette A.J.; De Deyn, Peter P.; Waninge, Aly; Dekker, Alain D.
ABSTRACT: Introduction: Observable dementia symptoms are hardly studied in people with severe/profound intellectual (and multiple) disabilities (SPI(M)D). Insight in symptomatology is needed for timely signaling/diagnosis. This study aimed to identify practice-based observations of dementia symptoms in this population. Methods: Care professionals and family members were invited to complete a survey about symptoms. Quantitatively analyzed survey data were further deepened through semi-structured interviews with care professionals having vast experience in signaling/diagnosing dementia in this population. Symptoms were categorized using a symptom matrix. Results: Survey respondents and interviewees frequently observed a decline in activities of daily living (ADL) functioning and behavioral and psychological changes, like increased irritability, anxiety, apathy and decreased eating/drinking behavior. Cognitive symptoms were particularly recognized in persons with verbal communication and/or walking skills. To lesser extent motor changes and medical comorbidities were reported. Conclusion: Increased insight in dementia symptoms contributes to developing a dedicated screening instrument for dementia in people with SPI(M)D.